Spectrophotometric Determination of Copper(II) Using Ammonium Pyrollidine Dithiocarbamate in Anionic Aqueous Solution of Sodium Dodecyl Sulphate - Afshan Soomro, Gul; Abbas Shar, Ghulam (Asian Journal of Chemistry, 2015)
A simple rapid new spectrophotometric method has been developed for the determination of copper using ammonium pyrollidine dithiocarbamate in presence of anionic aqueous micellar solution 1.0 % sodium dodecyl sulphate. Ammonium pyrollidine dithiocarbamate reacts with copper(II) to form bis(ammonium pyrollidine dithiocarbamato) copper complex. The importance of this method is the use of micellar system which replaces the previous solvent extraction steps. Micellar system enhancing the sensitivity, selectivity and the molar absorptivity which reduces the cost and toxicity. The average molar absorption coefficient and Sandell’s sensitivity was found to be 1.08 × 104 L mol-1 cm-1 and 5.83 ng cm-2 at lmax 447.8 nm respectively. Linear calibration graph was obtained over the concentration range 0.12-4.0 μg mL-1, the stoichiometric composition of the complex was 1:2 (Cu:[APDC]2. The developed method was successfully applied for the determination of copper from alloy and brass samples.